2001
DOI: 10.1002/j.2050-0416.2001.tb00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of (+)-Catechin and Ferulic Acid on Formation of Beer Haze and Their Removal through different Polyvinylpolypyrollidone-Types

Abstract: Tfte influence of (+)-catechin and ferulic acid on the formation of haze was investigated. Both phenolic compounds were added in different concentrations to beer before ageing through a force test. The removal of these compounds was observed by measuring the difference before and after forcing the beer. (+)-Catechin and ferulic acid shoived haze-decreasing as well as haze-increasing properties. The removal of (+)-catechin and ferulic acid from beer through three types of polyvinylpoUjpyrollidone (PVPP) at seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…It is of note that (+)-catechin caused the formation of hazes in much lower concentration than ferulic acid. Ferulic acid took part in the formation of colloidal hazes at higher concentrations, and this was dependent on different factors such as haze protein concentrations, pH, and the presence of other phenolic compounds 24 . The forcing experiments on beers with added ferulic acid or (+)-catechin showed that the carbonyl profile, a marker of lipid oxidation, was changed.…”
Section: Introductionmentioning
confidence: 99%
“…It is of note that (+)-catechin caused the formation of hazes in much lower concentration than ferulic acid. Ferulic acid took part in the formation of colloidal hazes at higher concentrations, and this was dependent on different factors such as haze protein concentrations, pH, and the presence of other phenolic compounds 24 . The forcing experiments on beers with added ferulic acid or (+)-catechin showed that the carbonyl profile, a marker of lipid oxidation, was changed.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption reaction in which PVPP forms hydrogen bonds with polyphenols is a reversible reaction. At increasing PVPP concentrations, the reaction balance is moved forward and TPC is reduced (Carrasco‐Sanchez et al., 2017; Papp et al., 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Der Großteil der heutzutage gebrauten Biere wird vor der Abfüllung filtriert, um Schwebstoffe (Apperson et al, 2002). Durch die Anwendung von PVPP können die Polyphenolgehalte des Bieres signifikant herabgesetzt werden, was meist in direkten Zusammenhang mit einer besseren Trübungsstabilität gebracht wird (McMurrough et al, 1992;McMurrough et al, 1996;Mikyška et al, 2002;Mikyška et al, 2019;Papp et al, 2001). Die Affinität von PVPP für Polyphenole wird der vermeintlichen Strukturähnlichkeit des synthetischen Kunststoffes mit Polyprolin zugeschrieben, einem Peptid, welches in einigen Modellsystemen zum Einsatz kommt, da es einen trübungsaktiven Charakter aufweist (Aron & Shellhammer, 2010;Schmidt, 2012).…”
Section: Filtration Und Stabilisierungunclassified